Criterios para la selección y uso de simulaciones en un grupo de profesores de Ciencias Naturales en formación - Bizzio, María de los Ángeles (2022)
In this paper we investigate the opinions of future teachers of Physics and Chemistry of the National University of San Juan (Argentina) about their experience in the use of simulations, the assessment they make about them and the criteria they would consider for their selection and use. The sample is made up of students who studied specific didactics during 2020. A questionnaire was designed to collect the data and, from the answers, categories were built for their analysis. The results show that the experience of the participants is associated with a low use of simulations, which would justify the need to deepen over the knowledge and use of simulations as a learning tool and as a resource for teaching from the initial teacher training